Agent Orange and the Prevalence of Cancer among the Vietnamese Population 30 Years after the End of the Vietnam War - Do, Quy-Toan (2012)
During the Vietnam War, more than 70 million liters of military herbicide were sprayed over the combat zone. This study uses self and proxy-reported data on cancer status obtained from a nationally representative health survey of the Vietnamese population (N=158,019), combined with measures of military herbicide exposure computed from detailed information on US and allied wartime military activities. No significant difference in the prevalence of reported cancer is detected between communes with some degree of exposure and those with none. When restricting the analysis to exposed communes and adopting a continuous measure of herbicide exposure, there is evidence of a dose-response relationship; among communes that were exposed, increasing exposure to past military spraying is associated with increasing prevalence of reported cancer in 2001-2002. There is mixed evidence as to whether cohorts born before or after the end of the spraying campaigns are equally affected.